Single Nucleotide Polymorphism Markers in Aedes aegypti Populations in Brazil - Paduan, K. S. [UNESP]; Ribolla, P. E. M. [UNESP] (Medimond S R L, 2008)
Single nucleotide polymorphisms (SNPs) were investigated in eighteen genes of sixteen populations of Aedes aegypti in Brazil. Eight SNP markers were selected in nine genes and surveyed in A. aegypti populations of three localities in different geographical locations. SNPs revealed significant genetic differentiation among populations recently analyzed by mitochondria DNA (mtDNA) and represented by a single genetic group (lineage). Results suggest that a haplotype derived from mtDNA analysis could be represented by different Aedes lineages revealed by SNP characterization. Genetic distances (pairwise F(ST)), AMOVA and cluster analyses indicated a high genetic structure for the A. aegypti populations investigated by SNPs. This set of SNP markers represents a useful tool for genetic studies in A. aegypti populations